Como erradicar o analfabetismo sem erradicar os analfabetos? - Munir Fasheh (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2004)
The text challenges various suppositions which are frequently included in official discussions on literacy, questioning the inherent liberating and positive value of the literacy process on the basis of the need to respect and valorise the diversity of forms of learning, studying, knowing and expressing oneself. It argues that liberation and liberty are linked to diversity and to pluralism and that education represents just one of the forms of learning. It affirms that universalism has been the principal cause of the elimination of diversity which is considered the essence of life and suggests that the adoption of literacy as the dominant form of knowledge could contribute to the disappearance of diversity and to the predominance of one path to progress and development.